The Combination of Medium and Method of Cultivation on The Growth Performance of Porphyridium cruentum - Hasanah, Hasanah; wulandari, Wulandari; afriani, Afriani; Hariski, M.; Muji Rahayu, Dyah; Arbajayanti, Rahma Dini (Program Pascasarjana Universitas Sriwijaya, 2025)
Porphyridium cruentum has advantages in pigments and exopolysaccharides, so it has the potential to be developed in the food, pharmaceutical, nutraceutical, and cosmetic industries. Porphyridium cruentum cultivation media uses synthetic and indoors, causing high costs. This study aims to determine the growth performance of Porphyridium cruentum in different mediums and method of cultivation. The research methods used cultivating Porphyridium cruentum for 7 days with four treatments, namely indoors Guillard media (IGM), outdoors Guillard media (OGM), indoors fertilizer media (IFM), and outdoors fertilizer media (OFM. Each treatment had three replications. Growth was identified using an optical density spectrophotometer uv-vis, gravimetrically dried weight of biomass and pH adjustment during 7 days of cultivation. The result shows the best growth performance in IFM, followed by IGM, OFM, and OGM. Fertilizer media is better for the growth of Porphyridium cruentum than Guillard media. pH growth Porphyridium cruentum during cultivation 7-7.5. Indoor cultivation is better than outdoor cultivation. The highest biomass was IFM, which had the best performance in IFM with OD 0.247, pH 7, and biomass 79.6%.